Characterization and application of nitrogen-fixing and indole-3-acetic acid producing bacteria A13 in Oil Palm (Elaeisguineensis Jacq.) seedling - Ismi Isti'anah; Nisa Rachmania Mubarik; Aris Tjahjoleksono (Journal of Microbial Systematics and Biotechnology, 2021)
Oil palm plantations have a good prospect in Indonesia. One of the efforts to improve the productivity of oil palm plantation is the application of bacteria as biological fertilizer. The research was conducted to characterize and apply the nitrogen-fixing and indole-3-acetic acid producing bacteria in oil palm seedlings. The bacteria was isolated from soil samples which taken from Taman Nasional Bukit Dua Belas (TNBD) Jambi. Nitrogen free bromthymol blue (NFB) is used as media for nitrogen-fixing bacterial isolation. Selected isolate named A13 had an ability to form white pellicle on the surface of the semisolid medium, increased the pH, and changed the color of medium from green to blue Isolate A13 was identified as Gram-negative bacteria and had a rods shape. Analysis of 16S rRNA gene sequence showed that isolate A13 had a similarity with Pseudochrobactrum assacharolyticum. Hypersensitivity assay on tobacco leaves showed that isolate A13 was not a pathogen. During 48 hours of incubation, isolate A13 produced a maximum of IAA at the 24th hour of incubation. Isolate A13 produced 0.675 ppm of ethylene/hour in Acetylene Reduction Assay and 69,839 ppm of IAA in HPLC methods. This was the first report on nitrogen fixation and IAA production by Pseudochrobactrum assacharolyticum and its application in the soil of oil palm seedlings. Application of isolate A13 in oil palm seedling increased significantly the number of lateral roots, stem diameter, and height of plants